Penyuluhan Melalui Teknik Games Mengenai Perencanaan Karir Lanjutan Mahasiswa Semester Akhir Akademi Pariwisata Pertiwi - Toto Raharjo; Dita Juwita Zuraida; Misbah Fikrianto (CV. Multi Kreasi Media, 2023)
Workplace is a place that students will enter after graduating from college. The many problems in the world of work make prospective workers must be more mature in planning careers in order to be able to face various challenges in the world of work. Knowledge about career planning is needed for prospective workers, including final year students of the Pertiwi Tourism Academy. One way to strengthen students about career planning is with lecture techniques accompanied by game techniques. The mentorship was attended by 21 eighth semester students of Pertiwi Tourism Academy. After the mentorship was carried out, the results showed that 61.4% of participants felt more inspired and had career planning after graduation.